Agricultural Productivity and Soil Carbon Dynamics: A Bioeconomic Model. (13th May 2019) - Berazneva, Julia; Conrad, Jon M; Güereña, David T; Lehmann, Johannes; Woolf, Dominic
Abstract: We examine the dynamic management of a soil resource—the issue at the core of both environmental and development challenges in developing countries. Our theoretical framework extends the traditional bioeconomic model of renewable resources to soil carbon management and investigates the effects of changes in agricultural practices on farmers' natural resource base and livelihoods. We parameterize the model using an eight-year panel data set from an agronomic experiment and data from household and market surveys in the western Kenyan highlands. The optimal maize yields and soil carbon stocks are higher than those observed in the region. This divergence is partly explained by farmers' heterogeneous time preferences (with the implied discount rates of 5% to 25%), information barriers, and market imperfections. The steady-state shadow price for soil carbon ranges from 95/Mg to 168/Mg, indicating a significant opportunity cost for soil mismanagement.